META-ANALISIS EFEKTIVITAS MODEL PEMBELAJARAN INQUIRY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA KELAS IV SD - Riski Aprilia Supusepa; Naomi Citra Permata Diaz; Yemima Dilla Sofy Nilasari (STKIP Subang, 2024)
ABSTRACT Mathematics learning plays an important role in shaping students' concept understanding and critical thinking skills. One of the learning models that has the potential to improve understanding of mathematical concepts is the guided inquiry learning model. This study used a meta-analysis method to investigate the effectiveness of guided inquiry learning model in improving mathematical problem solving skills in fourth grade students. Data were analyzed from various scientific articles and theses published between 2019 and 2024. The results of the meta-analysis show that the guided inquiry learning model significantly improves students' understanding of mathematical concepts with an effect size value that falls into the large effect category. The study also highlighted the importance of students' active role in learning, strengthening science process skills, and improving critical thinking ability. These findings provide strong support for the further implementation of the guided inquiry learning model in mathematics learning in primary schools. Therefore, the use of guided inquiry learning model can be an effective alternative in improving the quality of learning and students' mathematics achievement. ABSTRAK Pembelajaran matematika memegang peranan penting dalam membentuk pemahaman konsep serta keterampilan berpikir kritis siswa. Salah satu model pembelajaran yang memiliki potensi untuk meningkatkan pemahaman konsep matematis adalah model pembelajaran inkuiri terbimbing. Penelitian ini menggunakan metode meta-analisis untuk menyelidiki efektivitas penerapan model pembelajaran inkuiri terbimbing dalam meningkatkan kemampuan pemecahan masalah matematika pada siswa kelas IV SD. Data dianalisis dari berbagai artikel ilmiah dan skripsi yang dipublikasikan antara tahun 2019 hingga 2024. Hasil meta-analisis menunjukkan bahwa model pembelajaran inkuiri terbimbing secara signifikan meningkatkan pemahaman konsep matematis siswa dengan nilai effect size yang termasuk dalam kategori efek besar. Penelitian ini juga menyoroti pentingnya peran aktif siswa dalam pembelajaran, memperkuat keterampilan proses sains, dan meningkatkan kemampuan berpikir kritis. Temuan ini memberikan dukungan kuat terhadap implementasi lebih lanjut dari model pembelajaran inkuiri terbimbing dalam pembelajaran matematika di sekolah dasar. Oleh karena itu, penggunaan model pembelajaran inkuiri terbimbing dapat menjadi alternatif yang efektif dalam meningkatkan kualitas pembelajaran dan prestasi matematika siswa.